Osimertinib versus Standard of Care EGFR TKI as First-Line Treatment in Patients with EGFRm Advanced NSCLC: FLAURA Asian Subset - Byoung Chul Cho (2018)
© 2018 International Association for the Study of Lung Cancer Introduction: Here we report efficacy and safety data of an Asian subset of the phase III FLAURA trial (NCT02296125), which compares osimertinib with standard of care (SoC) EGFR tyrosine kinase inhibitors (TKIs) in patients with previously untreated advanced NSCLC with tumors harboring exon 19 deletion (Ex19del)/L858R EGFR TKI–sensitizing mutations. Methods: Eligible Asian patients (enrolled at Asian sites) who were at least 18 years of age (≥20 years in Japan) and had untreated EGFR-mutated advanced NSCLC were randomized 1:1 to receive osimertinib (80 mg, orally once daily) or an SoC EGFR TKI (gefitinib, 250 mg, or erlotinib, 150 mg, orally once daily). The primary end point was investigator-assessed progression-free survival (PFS). The key secondary end points were overall survival, objective response rate, central nervous system efficacy, and safety. Results: The median PFS was 16.5 versus 11.0 months for the osimertinib and SoC EGFR TKI groups, respectively (hazard ratio = 0.54, 95% confidence interval: 0.41–0.72, p < 0.0001). The overall survival data were immature (24% maturity). The objective response rates were 80% for osimertinib and 75% for an SoC EGFR TKI. The median central nervous system PFS was not calculable for the osimertinib group and was 13.8 months for the SoC EGFR TKI group (hazard ratio = 0.55, 95% confidence interval: 0.25–1.17, p = 0.118). Fewer adverse events of grade 3 or higher (40% versus 48%) and fewer adverse events leading to treatment discontinuation (15% versus 21%) were reported with osimertinib versus with an SoC EGFR TKI, respectively. Conclusion: In this Asian population, first-line osimertinib demonstrated a clinically meaningful improvement in PFS over an SoC EGFR TKI, with a safety profile consistent with that for the overall FLAURA study population.